2016
DOI: 10.1155/2016/2959763
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of a Magnetorheological Damper with Energy Harvesting Ability

Abstract: A magnetorheological (MR) damper with energy harvesting ability was proposed based on electromagnetic induction (EMI) principle. The energy harvesting part was composed of a permanent magnet array and inducing coils which move vertically. This device could act as a linear power generator when the external excitation was applied, and the kinetic energy could be converted into electrical energy due to the relative linear motion between the magnets array and the inducing coils. Finite element models of both the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…There were a permanent magnet, coil and energy storage section. The proposed MR damper force generate 750 N with 0.6 A current (Hu et al, 2016) Figure 7. Schematic diagram of MR damper with energy harvesting ability (Hu et al, 2016) The finite element analysis was carried out in Ansys software carries out for 3 similar models, it is fabricated and tested in vibration control laboratory.…”
Section: Analytical Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…There were a permanent magnet, coil and energy storage section. The proposed MR damper force generate 750 N with 0.6 A current (Hu et al, 2016) Figure 7. Schematic diagram of MR damper with energy harvesting ability (Hu et al, 2016) The finite element analysis was carried out in Ansys software carries out for 3 similar models, it is fabricated and tested in vibration control laboratory.…”
Section: Analytical Investigationmentioning
confidence: 99%
“…The proposed MR damper force generate 750 N with 0.6 A current (Hu et al, 2016) Figure 7. Schematic diagram of MR damper with energy harvesting ability (Hu et al, 2016) The finite element analysis was carried out in Ansys software carries out for 3 similar models, it is fabricated and tested in vibration control laboratory. A These findings will help car designers produce more effective and robust MR dampers and forecast their damping force features (Cai et al, 2002).…”
Section: Analytical Investigationmentioning
confidence: 99%
“…Using electromagnetic induction technique, an energy conserving device was suggested an electrical energy is developed, when external motion applied in between magnets and induced coils [31]. The self-power efficiency of the EMI, calculates the damping force, Figure 14 device produce approximately 750 N for 0.6 A current and 1 DC voltage [32].…”
Section: Addition Of Electromagnetic Induction Systemmentioning
confidence: 99%
“…Attention has been paid to magnetic fluid-based devices that can act as passive or active fluids assisting in the generation of different grades of damping power, reducing friction and assisting in heat dissipation, in order to avoid an increase in temperature from non-recovered energy. Significant work has also been carried out on magnetorheological dampers [ 9 , 10 ], and even with energy-harvesting ability [ 11 ]. Some studies can also be found on ferrofluids and their application on damping [ 12 ], their application to energy harvesting [ 13 ], and for their use in automotive applications [ 14 ].…”
Section: Introductionmentioning
confidence: 99%